A Comparative, Developmental, and Clinical Perspective of Neurobehavioral Sexual Dimorphisms - Viveros, Maria-Paz; Mendrek, Adrianna; Paus, Tomáš; Lopez Rodriguez, Ana Belen; Marco, Eva M.; Yehuda, Rachel; Cohen, Hagit; Lehrner, Amy; Wagner, Edward (Frontiers in Neuroscience, 2012)
Neurobiological mechanisms involved in sexual differentiation of the central nervous system will be presented with a comparative view across vertebrates. Women and men differ in a wide variety of behavioral traits and in the probabilities of developing certain mental disorders. A brief overview of sex-chromosome pathways underlying sexual dimorphisms will be provided. We will describe most common brain phenotypes derived in vivo with magnetic resonance imaging, discuss the challenges in interpreting these phenotypes vis-à-vis the underlying neurobiology and revise the known sex differences in brain structure from birth, through adolescence, to adulthood. Clinical and epidemiological data indicate important sex differences in the prevalence, course, and expression of psychopathologies such as schizophrenia, and mood disorders including major depression and bipolar illness. Recent evidence implies that mood disorders and psychosis share some common genetic predispositions, as well as some neurobiological basis. Therefore, modern research is emphasizing dimensional representation of mental disorders and conceptualization of schizophrenia, bipolar disorder and major depression as a continuum of cognitive deficits and neurobiological abnormalities. Herein, we have examined available evidence on cerebral sexual dimorphism in all three conditions to verify if sex differences vary quantitatively and/or qualitatively along the psychoses-depression continuum. Sex differences in posttraumatic disorders prevalence have also been described, thus data on differences at genomic and molecular levels will be considered. Finally, we will discuss the important contribution - advantages and limitations - of animal models in the investigation of underlying mechanisms of neurobehavioral sex differences in neuropsychiatric disorders, including drug dependence, with special emphasis in experimental models based on the neurodevelopmental and “three hits” hypotheses.